Contextual factors associated with smoking among Brazilian adolescents. Issue 8 (6th April 2011) - Barreto, Sandhi Maria; Giatti, Luana; Casado, Leticia; de Moura, Lenildo; Crespo, Claudio; Malta, Deborah
Abstract : Background: Very few studies have examined the role of school, household and family contexts in youth smoking in middle-income countries. Methods: This work describes smoking exposure among 59 992 high school students who took part in the Brazilian Survey of School Health and investigates contextual factors associated with regular smoking, defined as smoking cigarettes at least once in the past 30 days. The explaining variables were grouped into: socio-demographic characteristics, school context, household context and family rapport . Variables independently associated with smoking in each context were identified by multiple logistic regression analysis. Results: 53% of the total sample were girls, 89% were aged 13–15 years. 24% had already experimented with cigarettes, 50% before the age of 12 years. The prevalence of regular smoking was 6.3% (95% CI 5.87 to 6.74), with no sex variation. Smoking was not associated with either the mother's education or the index of household assets. In the multivariable analysis, studying at a private school, the possibility of purchasing cigarettes at school and skipping of classes without parents' consent increased the chances of smoking. In the household context, living with both parents was negatively associated with smoking, while having smoking parents and exposure to other people's smoking was positively related to smoking. In the family context, parental unawareness of what the adolescent was doing increased smoking, but having meals with the mother one or more days per week and parents' negative reactions to adolescent smoking reduced the chances of smoking. Conclusion: The results reinforce the role of school, household and family contexts in youth smoking behaviours and will help improve public health policies aimed at preventing smoking and health promotion in adolescents.